Mitochondrial metabolic regulation of macrophage polarization in osteomyelitis and other orthopedic disorders: mechanisms and therapeutic opportunities - Li, Jinglin; Zhang, Lin; Peng, Jiaze; Zhao, Chuntao; Li, Wenguang; Yu, Yang; Huang, Xianpeng; Yang, Fuyin; Deng, Xuan; Yang, Xuxu; Zhang, Tao; Peng, Jiachen (Frontiers in Cell and Developmental Biology, 2025)
Osteomyelitis is a complex infectious bone disease involving pathogen invasion, host immune responses, and dysregulation of the local microenvironment. As a critical component of the innate immune system, macrophages play a pivotal role in inflammatory responses and tissue repair. Their polarization states (M1/M2) directly influence disease progression, while mitochondrial metabolism, as the central hub of cellular energy metabolism, has recently been shown to play a key role in macrophage polarization and functional regulation. However, how mitochondrial metabolism regulates macrophage polarization to affect the pathological mechanisms of osteomyelitis, and how to develop novel therapeutic strategies based on this mechanism, remain critical scientific questions to be addressed. This review systematically summarizes the molecular mechanisms by which mitochondrial metabolism regulates macrophage polarization and its role in osteomyelitis, with a focus on the impact of mitochondrial dynamics (fission/fusion), metabolic reprogramming, and reactive oxygen species (ROS) generation on macrophage polarization. Additionally, potential therapeutic strategies targeting mitochondrial metabolism are analyzed. For the first time, this review integrates the interplay between mitochondrial metabolism and macrophage polarization in osteomyelitis, revealing how mitochondrial dysfunction exacerbates inflammation and bone destruction through metabolic reprogramming. Based on these findings, we propose novel therapeutic strategies targeting mitochondrial metabolism, offering new perspectives and directions for understanding the pathogenesis and clinical treatment of osteomyelitis.